Stars and stripes: hexatopic tris(3, 2′:6′, 3′′-terpyridine) ligands that unexpectedly form one-dimensional coordination polymers. Issue 3 (10th December 2021) - Manfroni, Giacomo; Prescimone, Alessandro; Constable, Edwin C.; Housecroft, Catherine E.
Abstract : Five hexatopic ligands containing 3, 2′:6′, 3′′- or 4, 2′:6′, 4′′-terpyridine domains are reported, along with the assembly of a 1D-coordination polymer consisting of alternating single and double loops. Abstract : The hexatopic ligands 1, 3, 5-tris(4, 2′:6′, 4′′-terpyridin-4′-yl)benzene (1 ), 1, 3, 5-tris(3, 2′:6′, 3′′-terpyridin-4′-yl)benzene (2 ), 1, 3, 5-tris4-(4, 2′:6′, 4′′-terpyridin-4′-yl)phenylbenzene (3 ), 1, 3, 5-tris4-(3, 2′:6′, 3′′-terpyridin-4′-yl)phenylbenzene (4 ) and 1, 3, 5-trimethyl-2, 4, 6-tris4-(3, 2′:6′, 3′′-terpyridin-4′-yl)phenylbenzene (5 ) have been prepared and characterized. The single crystal structure of 1 ·1.75DMF was determined; 1 exhibits a propeller-shaped geometry with each of the three 4, 2′:6′, 4′′-tpy domains being crystallographically independent. Packing of molecules of 1 is dominated by face-to-face π-stacking interactions which is consistent with the low solubility of 1 in common organic solvents. Reaction of 5 with [Cu(hfacac)2 ]·H2 O (Hhfacac = 1, 1, 1, 5, 5, 5-hexafluoropentane-2, 4-dione) under conditions of crystal growth by layering resulted in the formation of [Cu3 (hfacac)6 (5 )] n ·2.8 n C7 H8 ·0.4 n CHCl3 . Single-crystal X-ray diffraction reveals an unusual 1D-coordination polymer consisting of a series of alternating single and double loops. Each of the three crystallographically independent Cu atoms is octahedrally sited with cis -arrangements two N-donors from two different ligands 1 and, therefore, cis -arrangements of coordinated [hfacac] − ligands; this observation is unusual among compounds in the Cambridge Structural Database containing Cu(hfacac)2 N2 coordination units in which the two N-donors are in a non-chelating ligand.